Urinary tract stone deaths: data from the Australian and New Zealand Audits of Surgical Mortality. (6th August 2020) - Galiabovitch, Elena; Hansen, Dylan; Retegan, Claudia; McCahy, Philip
Abstract : Objectives: To analyse all mortalities related to surgery for urinary tract calculi in Australia from 1 January 2009 to 31 December 2018, and identify common causes, clinical management issues (CMIs), and areas for improvement. Patients and Methods: All urological‐related deaths reported to the Australian and New Zealand Audit of Surgical Mortality (ANZASM) from 2009 to 2017 were analysed. The Bi‐National Audit of Surgical Mortality (BAS) database was interrogated for any involvement with renal, ureteric or bladder stones and all relevant associated data analysed. Any CMIs documented by the peer reviewers were recorded and compared to those in urology and all of surgery ANZASM data. Results: Of 1034 total urological deaths, 100 (9.7%) were related to stones. The mean (range) age of patients was 74.4 (21–97) years; 95% of the patients underwent at least one procedure, with 45 (47.4%) of these being elective. Urinary sepsis was responsible for 49.5% of the deaths, with 20% dying of cardiac events. In all, 39% (37/95) of deaths were associated with CMIs, the most common considerations being delays in diagnosis or treatment, perioperative management and inadequate preoperative evaluation. This is a considerably higher percentage than the 26% recorded for the general urology and all surgery national data. Ureterorenoscopy at 54% (12/22) had the highest rate of CMIs. Conclusion: Death related to stone surgery represents only a small proportion of all urological surgical deaths, but generates more CMIs amongst ANZASM peer assessors. Results could be improved with more rapid diagnosis and treatment. Careful case selection and access to all treatment options are recommended.